Annual Plan 2005-06 Karnataka - Planning Commission (Planning Commission, 2005)
The outlay for the Annual Plan 2005-06 is Rs. 13555.00 crores. This represents an increase of 10.00% over the budgeted outlay of Rs. 12322.92 crores in 2004-05 and forms 31.1% of the Tenth Plan outlay of Rs.43558.22 crores. The District Plan size for Annual Plan 2005-06 is Rs.2002.89 crores. The outlay proposed for Externally Aided Projects in Annual Plan 2005-06 is Rs.2043.72 crores. Under the Special Component Plan Rs.628.80 crores have been earmarked for the welfare of the Scheduled Castes and Rs. 153.27 crores for the Scheduled Tribes under the Tribal Sub Plan.
Planning and Statistics Department